Queer lawfare in Africa: Legal strategies in contexts of LGBTIQ+ criminalisation and politicisation - Jjuuko, Adrian; Gloppen, Siri; Msosa, Alan; Viljoen, Frans (Pretoria University Law Press (PULP), 2022)
This book focuses on the strategies that activists for LGBTIQ+ equality in Africa deploy to challenge deep seated homophobia and transphobia, as well as the politicisation of LGBTIQ+ issues. It is a peer-reviewed, edited volume with scholarly contributions from lawyers, anthropologists, and LGBTIQ+ activists. It covers different country situations - those where equality is taking root, as the case is in South Africa, Botswana and Mozambique; those where homophobia reigns and LGBTIQ+ rights are politicised such as, Ghana, Kenya, Malawi, Nigeria, Senegal, Uganda, and Zambia; and those where traditional LGBTIQ+ activism is almost a nonstarter, such as in Ethiopia, Sudan and The Gambia.